Liposomal and Deoxycholate Amphotericin B Formulations: Effectiveness against Biofilm Infections of Candida spp. - Rodrigues, Célia F. (2017)
Background: candidiasis is the primary fungal infection encountered in patients undergoing prolonged hospitalization, and the fourth leading cause of nosocomial bloodstream infections. One of the most important Candida spp. virulence factors is the ability to form biofilms, which are extremely refractory to antimicrobial therapy and very difficult to treat with the traditional antifungal therapies. It is known that the prophylaxis or treatment of a systemic candidiasis are recurrently taken without considering the possibility of a Candida spp. biofilm-related infections. Therefore, it is important to assess the effectiveness of the available drugs and which formulations have the best performance in these specific infections. Methods: 24-h-biofilms of four Candida spp. and their response to two amphotericin B (AmB) pharmaceutical formulations (liposomal and deoxycholate) were evaluated. Results: generally, Candida glabrata was the less susceptible yeast species to both AmBs. MBECs revealed that it is therapeutically more appealing to use AmB-L than AmB-Deox for all Candida spp. biofilms, since none of the determined concentrations of AmB-L reached 10% of the maximum daily dose, but both formulations showed a very good capacity in the biomass reduction. Conclusions: the liposomal formulation presents better performance in the eradication of the biofilm cells for all the species in comparison with the deoxycholate formulation.